Changes in Air Pollution Following the COVID-19 Epidemic in Northern China: The Role of Meteorology - Xian, Tian; Li, Zhanqing; Wei, Jing (Frontiers in Environmental Science, 2021)
COVID-19 has a tremendous impact on both human life and the environment due to the unprecedented large-scale shutdown of economic activities at the beginning of 2020. While it was widely expected to see a dramatic reduction in air pollution, reality appears to be much more complex due to the joint influences of emissions and meteorology in dictating air pollution. By analyzing ample meteorological and environmental observational data, this study attempts to evaluate the contribution of an economic lockdown or at a well-below normal level across China to air pollution during the COVID-19 pandemic in the Beijing-Tianjin-Hebei region. Besides the unprecedented emission reductions that helped to improve air quality, multiple other factors came into play, such as high humidity and low wind speed that are favorable for haze formation. After separating long-term trends, seasonal signals, holiday effects, and meteorological contributions concerning climatology, we estimated that the relative contributions of human activities to changes in particulate matter with a diameter of less than 2.5μm and nitrogen dioxide during the epidemic were -17.13μg/m3 and -0.03μg/m3, respectively, with negative quantities denoting reductions to air pollution. Furthermore, comparing the changes in PM2.5 and NO2 concentrations after lockdown revealed that for short-term control measures, meteorological factors mainly affected pollutant particles.